2022
DOI: 10.5209/rlog.76701
|View full text |Cite
|
Sign up to set email alerts
|

Diseño y validación de una escala vocal multidimensional para la detección del riesgo vocal en docentes

Abstract: En el colectivo docente es frecuente el mal uso de la voz, para preservar su salud vocal es necesario un diagnóstico precoz. El objetivo del estudio fue diseñar, según criterios de especificidad y sencillez, una escala vocal multidimensional y fiable que contribuya a detectar situaciones de riesgo vocal del docente en el contexto escolar (EVM-D). Participaron 299 docentes, de 18 centros educativos de A Coruña seleccionados aleatoriamente, se dividieron en dos submuestras, una (n =143) para la realización del a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
1
1
0
2
Order By: Relevance
“…Other authors reported that dysphonia is more common among female teachers, particularly at the beginning of their profession [47]. In this sense, in both the validation study of the EVM-D scale [30] and the present study, the means in all dimensions of this scale tended to be higher among women who had more hours of weekly teaching. By contrast, the variable number of teaching hours per week was not associated with a higher vocal risk, as assessed by the EVM-D.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Other authors reported that dysphonia is more common among female teachers, particularly at the beginning of their profession [47]. In this sense, in both the validation study of the EVM-D scale [30] and the present study, the means in all dimensions of this scale tended to be higher among women who had more hours of weekly teaching. By contrast, the variable number of teaching hours per week was not associated with a higher vocal risk, as assessed by the EVM-D.…”
Section: Discussionsupporting
confidence: 62%
“…To analyze vocal problems, the EVM-D (acronym in Spanish) was used. This vocal scale was validated by García-Real et al [30] and designed with teachers from Galicia, Spain, to identify vocal risk based on self-reported etiological factors and symptoms associated with voice problems. This vocal scale features 12 items divided into three dimensions.…”
Section: Instruments and Proceduresmentioning
confidence: 99%
“…La disfonía ocupacional es un problema de salud pública, que se enmarca en el seguro contra accidentes del trabajo y enfermedades profesionales, definidas bajo la ley 16.744 de la constitución chilena (Establece normas sobre accidentes del trabajo y enfermedades profesionales, 1968). Esta patología se origina en personas que usan su voz con un objetivo laboral por períodos prolongados, siendo los profesores la primera categoría profesional en riesgo de contraerla según la Organización Internacional del Trabajo (García-Real et al, 2022).…”
Section: Introductionunclassified
“…Dada la frecuencia de los problemas de voz en la población docente es necesario disponer de un instrumento sencillo, que posea un número reducido de ítems y que permita detectar las situaciones de riesgo vocal de forma fácil y rápida. Ello ayudaría a prevenir las dificultades de la voz y a adoptar programas de higiene vocal (García-Real et al, 2022). Toda medida preventiva parte desde el conocimiento y reconocimiento de síntomas.…”
Section: Introductionunclassified